The Impact of Management Information Systems on Employee Work Productivity in the Digital Era - Wisnu Saputra; Muhammad Fahmi; Ragil Fadhilah Akhdan; Muhammad Ilham; Muhammad Bimo Tri Nugroho; Ahmad Nursodiq (Jurnal Multidisiplin Sahombu, 2026)
The development of digital technology has encouraged organizations to utilize Management Information Systems (MIS) to support operational activities and enhance employee performance. The use of MIS is expected to improve work productivity by providing faster, more accurate, and well-organized information. This study aims to examine the effect of Management Information Systems on employee work productivity in the digital era. The research employs a descriptive quantitative approach, with data collected through questionnaires distributed to employees in organizations that have implemented MIS. The data were analyzed descriptively to assess the relationship between MIS usage and employee productivity. The results indicate that the implementation of Management Information Systems has a positive impact on work efficiency and helps employees complete tasks more effectively. Therefore, Management Information Systems can be considered a key supporting factor in improving employee productivity in the digital era.